Anthropogenic noise and atmospheric absorption of sound induce amplitude shifts in the songs of Southern House Wren (Troglodytes aedon musculus) - Sementili-Cardoso, Guilherme; Donatelli, Reginaldo José (Urban ecosystems, 2021)
Birdsong is an important feature that mediates several aspects of bird reproduction, such as mate choice, territory defense, and individual recognition. Any factor that impairs vocal transmission through the environment may also impair conspecific recognition and thus reduce the effectiveness of reproduction. In this scenario, birds inhabiting urban environments might be subject to different selective pressures on their vocal amplitude due to acoustic barriers in the song transmission, such as excessive background noise and abnormal atmospheric absorption of sound. Therefore, we measured the amplitude of the song of the Southern House Wren ( Troglodytes aedon musculus ), to determine the relationships between the variation in vocal intensity and the environmental features. We expect divergence in vocal amplitude according to the noise levels, with song intensity responding to the increasing noise. We found that birds sang with higher amplitude in areas where traffic noise is elevated. Multiple linear regression showed a positive relationship between song amplitude and background noise and a negative relationship between vocal intensity and atmospheric attenuation. Our findings suggest a direct influence of urban environmental structures on the vocal behavior of wrens, which may challenge the effectiveness of communication between subjects and affect the behavioral ecology of the species.